Where There's Smoke, There's Fire? Significance of Atrial Fibrillation in Young Patients - Wutzler, Alexander (Clin Cardiol, 2016)
BACKGROUND: Atrial fibrillation (AF), a disease of the elderly, occasionally occurs at younger age. Pathophysiology of AF in younger patients is diverse, including channelopathies and cardiomyopathies. Data on the significance and complications of AF in young patients are scarce. HYPOTHESIS: Atrial fibrillation is the first manifestation of cardiovascular disease (CVD) in young patients. METHODS: From 11 888 patients in a university hospital database, patients age ≤35 years were identified. A composite of stroke/transient ischemic attack, thromboembolic events, major bleeding, and death was the primary endpoint. Stroke/transient ischemic attack, thromboembolic events, major bleeding, death, AF during follow‐up, diagnosis of arrhythmia other than AF, and new diagnosis of any CVD were secondary endpoints. Endpoints were compared between patients with and without comorbidities. RESULTS: We identified 124 patients (29.1± 5 years). Of those, 84 were followed over 48.4 ± 39.8 months. Comorbidities were present in 40.5%. Incidence of the primary endpoint was not different between the groups. Arrhythmias other than AF were more common in patients without comorbidities (36% vs 14.7%; P = 0.032). A supraventricular tachycardia (SVT) was found in 57.1% of patients who underwent electrophysiological testing and was treated with catheter ablation. None of those patients had AF during follow‐up. CONCLUSIONS: Atrial fibrillation occurs in young patients with and without structural heart disease. Young AF patients without comorbidities rarely develop CVD during the first years after diagnosis. Yet, an SVT is found in a high proportion of young AF patients; AF may be first manifestation of SVT. Therefore, young patients should undergo further evaluation for SVT